Beneficial effects of LRP6-CRISPR on prevention of alcohol-related liver injury surpassed fecal microbiota transplant in a rat model. (3rd July 2020) - Yu, Linghua; Wang, Linlin; Yi, Huixing; Wu, Xiaojun
ABSTRACT: Alcohol intake can modify gut microbiota composition, increase gut permeability, and promote liver fibrogenesis. LRP6 is a signal transmembrane protein and a co-receptor for the canonical Wnt signaling pathway. This study compared the curative effect of LRP6-CRISPR on alcohol-related liver injury with that of traditional fecal microbiota transplant (FMT) and investigated the alteration of the gut microbiome following the treatment. A rat model of alcohol-related liver injury was established and injected with lentiviral vectors expressing LRP6-CRISPR or administered with fecal filtrate from healthy rats, with healthy rat served as the control. Liver tissues of rats were examined by HE staining, Sirius staining, and Oil red O staining, respectively. The expression of LRP6 and fibrosis biomarkers were tested by PCR. The fecal sample of rats was collected and examined by 16S rRNA sequencing. Our data indicated that LRP6-CRISPR was more efficient in the prevention of alcohol-related liver injury than FMT. Microbiome analysis showed that alcohol-related liver injury related to gut microbiota dysbiosis, while treatment with LRP6-CRISPR or FMT increased gut microflora diversity and improved gut symbiosis. Further, bacteria specific to the disease stages were identified. Genera Romboutsia, Escherichia-Shigella, Pseudomonas, Turicibacter, and Helicobacter were prevalent in the intestine of rats with alcohol-related liver injury, while the domination of Lactobacillus was found in rats treated with LRP6-CRISPR or FMT. Besides, Lactobacillus and genera belonging to family Lachnospiraceae, Bacteroidales S24-7 group, and Ruminococcaceae were enriched in healthy rats. LRP6-CRISPR and FMT have beneficial effects on the prevention of alcohol-related liver injury, and correspondently, both treatments altered the disrupted gut microflora to a healthy one.